AN ANALYSIS OF TEACHER’S CLASSROOM MANAGEMENT IN LANGUAGE TEACHING AT MA AL-ISLAM JAMSAREN SURAKARTA - Fithriyah Nurul Hidayati; Saskia Putri Wardani (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
The purpose of this research is to describe the components of classroom management implemented by the teacher in English language teaching at the eleventh grade of MA Al-Islam Jamsaren Surakarta in the academic year of 2024/2025. The design of the research was descriptive qualitative research. The research subjects were one English teacher and students of XI-3, MA Al-Islam Jamsaren Surakarta. The data were collected by interview, observation, and documentation. The data were analysed by Miles, Huberman, and Saldana's model. In the trustworthiness of the data, this research uses triangulation by method. The result of this study indicates that the component of classroom management used by English teacher in teaching English at class XI-3 of MA Al Islam Jamsaren Surakarta academic year 2024/2025 divided into five components: creating and teaching expectations and rules (examine the need for rules, select the rules, teach and review the rules, and obtain commitments), establishing procedures and structures (making management instructional preparations, organizing classroom and materials, and procedures in the classroom), reinforcing expectations (building positive teacher-student relationships, having mental set for management, managing whole-group instruction, maintaining student attention and involvement, and improving classroom climate with reinforcers), actively engaging students (planning decisions affect behaviour management, managing lesson delivery, and managing student work), and managing misbehavior (situational assistance, mild responses, and moderate responses).